Konsep wali nikah dalam perspektif ulama klasik dan modern - Faizah, Nur (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2024)
This paper explores the concept of marriage guardian in Islamic jurisprudence by examining its interpretation and application by scholars from classical schools such as Hanafi, Maliki, Shafi'i and Hanbali, and comparing it with the views of contemporary scholars. The role of the marriage guardian is very important in the Islamic marriage contract, especially as it usually involves a male guardian consenting to a girl's marriage. The study also examines the perspectives of modern scholars who consider the evolving context of society, gender equality and women's autonomy. By comparing classical and modern interpretations, this study highlights the dynamic nature of Islamic legal thought as well as the ongoing discourse regarding the balance between traditional values and modern principles of individual rights and freedoms. The analysis aims to provide a comprehensive understanding of the role of marriage guardians, its historical roots and its relevance in today's socio-legal landscape.